APPLICATION OF THE STAD LEARNING MODEL IN SCIENCE LEARNING TO IMPROVE THE INTEREST AND LEARNING OUTCOMES OF STUDENTS IN CLASS V ELEMENTARY SCHOOL IN BARUGBUG 1 DISTRICT PADARINCANG - Mawan, Hermawan; Saefurahman, Asep (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2024)
This study used the STAD (Student Teams Achievement Division) Learning Model in Natural Science Learning to Increase Interest and Learning Outcomes of Fifth-Grade Students at Elementary School Barugbug 1, Padarincang District. The study aimed to determine the interest and learning outcomes of students by applying the STAD model in science lessons on the topic of the human respiratory system. The subjects of the research were 40 fifth-grade students at Elementary School Barugbug 1, consisting of 21 male and 19 female students. The research was conducted from March to May 2022, using a classroom action research method. Initially, the students were still passive, and the learning process was teacher-centered, with the first cycle showing some student engagement, though not comprehensive. The post-test result in the first cycle was 78.63, which increased to 89.12 in the second cycle. In the second cycle, students became more active, responsive, and collaborative. The interest questionnaire result increased from 57.5 in Cycle I to 80.62 in Cycle II.